ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI MASYARAKAT DALAM KEPESERTAAN BPJS KESEHATAN DI DESA PERSADANTA KECAMATAN BARUSJAHE KABUPATEN KARO TAHUN 2024 - Naftalia Keliat, Fani; Manurung, Jasmen; Sinaga, Janno; Tarigan, Frida Lina (Akupun Tour Publisher, 2024)
Background: Community participation in BPJS Health membership is uneven between the two hamlets that are part of Persadanta Village in participating in the BPJS Health program. There are 33% of the Persadanta Village community who have not participated in the BPJS Health program. The community has not participated in the BPJS Health program because the community feels that there are still other needs to be met and considers BPJS Health not the main need. Purpose: Meanwhile, to get health protection in living life, health insurance such as BPJS Health is needed to help anticipate and minimize the financial impact of various life risks that can occur at any time. Method: This study aims to analyze the relationship between education level, economic status, knowledge, attitudes and community perceptions with BPJS Health membership participation in Persadanta Village. By using quantitative research with a cross sectional design, researchers analyzed data from 79 heads of households obtained through questionnaires and interviews. Data were analyzed using the chi-square test with a 95% confidence level. Disscusion and Conclusion: Through statistical tests, it was found that all variables were associated with BPJS Health membership participation in Persadanta Village. Seeing the importance of being a BPJS Health participant, a series of policies are needed to increase the participation of the Persadanta Village community in participating in the BPJS Health program.